Rotation, spectral variability, magnetic geometry and magnetosphere of the Of?p star CPD -28° 2561 - Wade, G. A. (2015)
We report magnetic and spectroscopic observations and modelling of the Of?p star CPD-28° 2561. Using more than 75 new spectra, we have measured the equivalent width variations and examined the dynamic spectra of photospheric and wind-sensitive spectral lines. A period search results in an unambiguous 73.41 d variability period. High-resolution spectropolarimetric data analysed using least-squares deconvolution yield a Zeeman signature detected in the mean Stokes V profile corresponding to phase 0.5 of the spectral ephemeris. Interpreting the 73.41 d period as the stellar rotational period, we have phased the equivalent widths and inferred longitudinal field measurements. The phased magnetic data exhibit a weak sinusoidal variation, with maximum of about 565 G at phase 0.5, and a minimum of about -335 G at phase 0.0, with extrema approximately in phase with the (double-wave) Hα equivalent width variation. Modelling of the Hα equivalent width variation assuming a quasi-3D magnetospheric model produces a unique solution for the ambiguous couplet of inclination and magnetic obliquity angles: (i, β) or (β, i) = (35°, 90°). Adopting either geometry, the longitudinal field variation yields a dipole polar intensity Bd = 2.6 ± 0.9 kG, consistent with that obtained from direct modelling of the Stokes V profiles. We derive a wind magnetic confinement parameter η* ≃ 100, leading to an Alfvén radius RA ≃ 3-5R*, and a Kepler radius RK ≃ 20R*. This supports a physical scenario in which the Hα emission and other line variability have their origin in an oblique, corotating 'dynamical magnetosphere' structure resulting from a magnetically channelled wind. Nevertheless, the details of the formation of spectral lines and their variability within this framework remain generally poorly understood.